Hur många jobb skapas av gruvindustrin i norra Sverige? : En ekonometrisk studie - Moritz, Thomas (2015)
The purpose of this study is to assess the effects of the mining industry in northern Sweden by examining the job multiplier. The multiplier shows how many jobs that are created in other sectors in the region, as one new job in the mining industry is created. The job multiplier will be estimated for different parts of northern Sweden. To estimate the job multiplier an econometric model introduced by Moretti (2010) will be applied. Data on the number of employees in different sectors in northern Sweden was collected from the Central Bureau of Statistics in Sweden. The result shows that between 0.492 and 0.662 new jobs in the private service sector is created for each new job in the mining sector. The results vary depending on which municipalities in northern Sweden that are included. It also shows that totally between 0.852 and 0.989 new jobs are created for each new mining job, when all sectors are combined into one sector. Finally, the study shows that municipalities with mining employees are more affected by the mining industry than municipalities without mining workers. Validerat; 20150616 (global_studentproject_submitter)